1995
DOI: 10.1136/vr.136.13.319
|View full text |Cite
|
Sign up to set email alerts
|

Effects on cattle of transport by road for up to 15 hours

Abstract: Twenty-four castrated male cattle aged between 12 and 18 months were transported by road for five, 10 or 15 hours, over distances of 286, 536 and 738 km. Half the animals were of Hereford x Friesian breeding and half of 'continental' type. The animals transported for five hours lost 4.6 per cent of their bodyweight, those transported for 10 hours lost 6.5 per cent and those transported for 15 hours lost 7.0 per cent; recovery to pre-transport values took five days. There was little evidence from changes in blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
104
2
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 0 publications
15
104
2
12
Order By: Relevance
“…In our study, CK was similar between transport times, suggesting that minimal muscle trauma had occurred during transport and handling and that the experiment was carried out in good conditions. Furthermore, Warriss et al (1995) showed in cattle that plasma CK activity increased commensurate with journey duration, suggesting that maintenance of posture in the moving vehicle is physically demanding. Whereas, Warriss et al (1995) studied transport length up to 15 h, the 5 h transport time in the present experiment may not be long enough to increase plasma CK activity or because the stress response of lambs differed to cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, CK was similar between transport times, suggesting that minimal muscle trauma had occurred during transport and handling and that the experiment was carried out in good conditions. Furthermore, Warriss et al (1995) showed in cattle that plasma CK activity increased commensurate with journey duration, suggesting that maintenance of posture in the moving vehicle is physically demanding. Whereas, Warriss et al (1995) studied transport length up to 15 h, the 5 h transport time in the present experiment may not be long enough to increase plasma CK activity or because the stress response of lambs differed to cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Warriss et al (1995) showed in cattle that plasma CK activity increased commensurate with journey duration, suggesting that maintenance of posture in the moving vehicle is physically demanding. Whereas, Warriss et al (1995) studied transport length up to 15 h, the 5 h transport time in the present experiment may not be long enough to increase plasma CK activity or because the stress response of lambs differed to cattle. Cockram et al (1999) observed no significant differences in CK activity in lambs transported for 15 h compared to non-transported lambs, because in the transported lambs, the number of potentially traumatic events was low.…”
Section: Discussionmentioning
confidence: 99%
“…In young and older cattle, cortisol concentration is reported to increase following loading, during the first part of a journey and after unloading (Warriss et al, 1995;Knowles, 1999). Furthermore, Warriss et al (1995) reported that while plasma cortisol concentrations increased in cattle following loading, values returned to normal as the journey continued. In contrast, Tarrant et al (1992) and Dixit et al (2001) reported that for cattle, the actual journey was more stressful than loading and unloading.…”
Section: Physiological Effects Of Transportation Stress On Cattlementioning
confidence: 98%
“…Extensively raised animals exhibit more psychological or fear stress during loading and unloading compared with more intensively reared animals (Grandin, 1997). In young and older cattle, cortisol concentration is reported to increase following loading, during the first part of a journey and after unloading (Warriss et al, 1995;Knowles, 1999). Furthermore, Warriss et al (1995) reported that while plasma cortisol concentrations increased in cattle following loading, values returned to normal as the journey continued.…”
Section: Physiological Effects Of Transportation Stress On Cattlementioning
confidence: 99%
See 1 more Smart Citation